2017
DOI: 10.1371/journal.pgen.1006720
|View full text |Cite
|
Sign up to set email alerts
|

A Wnt-planar polarity pathway instructs neurite branching by restricting F-actin assembly through endosomal signaling

Abstract: Spatial arrangement of neurite branching is instructed by both attractive and repulsive cues. Here we show that in C. elegans, the Wnt family of secreted glycoproteins specify neurite branching sites in the PLM mechanosensory neurons. Wnts function through MIG-1/Frizzled and the planar cell polarity protein (PCP) VANG-1/Strabismus/Vangl2 to restrict the formation of F-actin patches, which mark branching sites in nascent neurites. We find that VANG-1 promotes Wnt signaling by facilitating Frizzled endocytosis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 55 publications
1
34
0
Order By: Relevance
“…The frequency of actin trails is 5 ± 0.42/100 μm/minute (Figure S2F) and their velocity of extension is 0.42 ± 0.02 μm/s (Figure S2G). We also used Coronin‐1::mCherry (COR‐1), an orthologue of a mammalian actin‐binding protein associated predominantly with F‐actin, that is also known to cross‐link actin and microtubules in yeast . About half of the utCH‐rich regions are enriched with COR‐1 as well (Figure S3A,B).…”
Section: Resultsmentioning
confidence: 99%
“…The frequency of actin trails is 5 ± 0.42/100 μm/minute (Figure S2F) and their velocity of extension is 0.42 ± 0.02 μm/s (Figure S2G). We also used Coronin‐1::mCherry (COR‐1), an orthologue of a mammalian actin‐binding protein associated predominantly with F‐actin, that is also known to cross‐link actin and microtubules in yeast . About half of the utCH‐rich regions are enriched with COR‐1 as well (Figure S3A,B).…”
Section: Resultsmentioning
confidence: 99%
“…Aliceblue was also significantly enriched for the syndecan-2 signaling pathway, and contained the SDC2 gene itself, which functions in dendritic structural changes together with F-actin [48]. Additionally, the most significant enrichment group unique to Cadetblue was the Wnt signaling pathway, which also regulates actin function [49, 50]. Of note, a prior study has shown that ARRB2 (a Cadetblue hub gene and member of Wnt signaling pathway) knockout rats display significantly decreased levels of voluntary ethanol consumption and psychomotor stimulation in response to ethanol [51].…”
Section: Discussionmentioning
confidence: 99%
“…The PLM synaptic branches are formed in a stereotypical position along the main axon shaft. This is controlled by Wnt-Frizzled and Planar Cell Polarity signalling pathways that function to spatially restrict the focal accumulation of filamentous (F-) actin [40]. To examine whether MEC-17 is important for developmental patterning of the branch, we calculated the relative position of the branch to the cell body and axon terminus.…”
Section: Misregulation Of Mec-17 Disrupts Synaptic Branch Developmentmentioning
confidence: 99%